2009
DOI: 10.1038/ncb2004
|View full text |Cite
|
Sign up to set email alerts
|

Cdk2 suppresses cellular senescence induced by the c-myc oncogene

Abstract: Activated oncogenes induce compensatory tumour-suppressive responses, such as cellular senescence or apoptosis, but the signals determining the main outcome remain to be fully understood. Here, we uncover a role for Cdk2 (cyclin-dependent kinase 2) in suppressing Myc-induced senescence. Short-term activation of Myc promoted cell-cycle progression in either wild-type or Cdk2 knockout mouse embryo fibroblasts (MEFs). In the knockout MEFs, however, the initial hyper-proliferative response was followed by cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
194
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(214 citation statements)
references
References 52 publications
17
194
2
1
Order By: Relevance
“…CDK2 plays a redundant role in cell division and mouse development in normal physiologic process (43,44). But recently, some research showed that CDK2 plays a crucial, nonredundant function in tumor cell senescence (45,46). By using multiple independent analyses, we determined that miR-200c specifically and negatively regulates CDK2 in vitro and in vivo, while miR-200c and CDK2 are antagonistic to each other can mutually reverse the tumorigenic effects conferred by the other.…”
Section: Discussionmentioning
confidence: 95%
“…CDK2 plays a redundant role in cell division and mouse development in normal physiologic process (43,44). But recently, some research showed that CDK2 plays a crucial, nonredundant function in tumor cell senescence (45,46). By using multiple independent analyses, we determined that miR-200c specifically and negatively regulates CDK2 in vitro and in vivo, while miR-200c and CDK2 are antagonistic to each other can mutually reverse the tumorigenic effects conferred by the other.…”
Section: Discussionmentioning
confidence: 95%
“…Along these lines, Lin et al (2010) reported that a Skp2-SCF inhibitor triggers senescence and inhibition of tumor growth of PTEN-deficient cancer cells. In further support of this emerging theme, Amati and colleagues (Campaner et al 2010) observed that oncogenic stress caused by the Myc oncoprotein sensitizes Cdk2-deficient cells to undergo senescence in vitro and in vivo. Similarly, in advanced non-small-cell lung carcinoma driven by activation of oncogenic KRas, tumor progression is halted and senescence is induced upon genetic ablation of Cdk4 (Puyol et al 2010).…”
Section: Restoration Of Cellular Senescence In Vivomentioning
confidence: 88%
“…12). Synthetic lethal interactions allow the elimination of tumour cells carrying genetic lesions that cannot be targeted using small molecules [23][24][25][26][27][28] . We show that elevated energy consumption and addiction to mitochondrial glutaminolysis in cells expressing deregulated MYC establish a dependence on the kinase ARK5, which limits mTORC1 activity and maintains a high respiratory capacity.…”
Section: Research Lettermentioning
confidence: 99%